THE EFFECT OF PENS STRATEGY ON STUDENTS’ ABILITY IN WRITING AT SMP IT MADANI PEKANBARU - Sihombing, Fadliana; Erni, Erni; Masyhur, Masyhur (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: This research is aimed to find out whether or not there is significant effect of PENS strategy on students’ ability at SMP IT Madani Pekanbaru in Writing. The research design is a pre-experimental research with one group pre-test and post-test design. The sample was all of students VIII. In order to collect the data, the pre-test and post-test were administered and then the data were statistically analyzed by using the t-test formula. The result showed that the mean score of post-test was higher than mean score of pre-test (67.61 > 59.68). The value of t-test was 11.360 while the value of t-table in significance level 5% df = 34 was 2.032. Since the value of the t-test was higher than t-table, it can be concluded that Alternative Hypothesis (Ha) was accepted and Null Hypothesis (Ho) was rejected. It means that there was significant effect of PENS strategy on students’ ability in writing at SMP IT Madani Pekanbaru.Key Words: Effect, PENS strategy, Writing Ability